Regulatory Mechanism of PD-L1 Expression in Primary Liver Cancer - LI Shenghao (Magazine House of Cancer Research on Prevention and Treatment, 2021)
The application of immunotherapy has become a hot spot in tumor research currently. In particular, immune checkpoint inhibitors have played an important role in the treatment of advanced unresectable primary liver cancer. However, the efficacy of immune checkpoint inhibitors varies greatly in the treatment of different patients, which has aroused people's attention to the regulatory mechanism of PD-L1 in the immune escape of liver tumors. PD-L1 is regulated by multiple levels and multiple signaling pathways in liver cancer, including gene mutation, epigenetic mechanisms, transcriptional regulation, post-transcriptional regulation and post-translational modification. Studies have also found that the high expression of PD-L1 may be the main factor affecting the immunotherapy of primary liver cancer. Therefore, it can provide more evidence for immunotherapy and immune combination therapy strategies of primary liver cancer by clarifying the regulatory mechanism of PD-L1.